Entrances and exits - Richards, Michael, 1949- (Permuted Press, 2024)
In this memoir, the author writes about the evolution of Cosmo Kramer, his character on Seinfeld, sharing insecurities and successes he experienced creating the character. He discusses his childhood with his schizophrenic grandmother and single mother, and his drive to unravel the mystery of his father. He tells of his early passion for theater and performance, his tour of duty in the army, his interest in psychology and religion, and his days coming up in LA's comedy clubs with Robin Williams, Andy Kaufman and Sam Kinison. He also opens up about the night of outrageous anger in a comedy club that resulted in nearly two decades of self exile.